MADURESE WOMEN AND BINDING CULTURE IN MUNA MASYARI’S MARTABAT KEMATIAN: GYNOCRITICISM ANALYSIS - Hartanto, Erika Citra Sari; Roifah, Miftahur (Faculty of Humanities, Diponegoro University, 2020)
Muna Masyari is a famous female author from Pamekasan, Madura, whose one of her short stories, Sortana, won an award from Kompas, a national newspaper, as the best short story in 2017. Through her short stories, she consistent in depicting the social problems, particularly, related to Madurese women. This article discusses the portrayal of Madurese women in four short stories, namely Kembang Pengantin, Rumah Hantaran, Are’ Lancor, and Topeng Gelur. This article focuses on Madurese women as daughter and mother and their relation to nature and oppressed culture. This study uses descriptive approach with close reading method. Data collection is in the form of words and the data analysis is done by interpreting the data based on Elaine Showalter’s Gynocriticism which concerns with women as writer as well as the producer of literary texts. Gynocriticism mostly deals with four models; they are women’s writing and women’s body, women’s writing and women’s language, women’s writing and women’s psyche, and women’s writing and women’s culture. The results show Masyari reveals many problems attached to Madurese women through women’s body, language, psyche and culture. Madurese early arranged marriage and myths has placed Madurese women in oppressive and unfortunate conditions due to the binding culture that has dominated women. Muna Masyari, yet, places her female characters who are daring to speak their voice to have their own authority in searching their destiny in the future.